Subjectively‐defined optimal/non‐optimal time of day modulates controlled but not automatic retrieval processes in verbal memory. (28th November 2018) - Puttaert, Delphine; Adam, Stéphane; Peigneux, Philippe
Abstract: Performance for controlled, resource‐demanding retrieval in episodic memory has been consistently found to be better at an optimal compared with non‐optimal time of the day, evidencing a synchrony effect. However, performance in memory tasks in which retrieval is mostly based on automatic processes was inconclusively found either to be better at a non‐optimal time of day or independent of synchrony effects. A caveat in most prior studies is that optimal/non‐optimal time of day is based on morningness–eveningness composite scores derived from chronotype questionnaires, which might not efficiently predict subjectively‐defined cognitive efficiency periods. An additional caveat is that separate tasks are used to assess explicit and implicit retrieval in verbal memory. Indeed, no task is process‐pure, and both controlled and automatic retrieval processes may potentially contribute to retrieval scores in different types of memory tasks. In the present study, we investigated the impact of individually defined subjective optimal/non‐optimal time of day on verbal memory retrieval, using an adaptation of the Process‐Dissociation Procedure that allows estimating the respective contributions of automatic and controlled memory retrieval processes within the same memory task. Our results disclose a higher involvement of controlled processes at subjectively optimal compared with non‐optimal time of day, but no differences for automatic processes. Synchrony effects and subjectively‐defined peaks and troughs of performance for controlled components of memory retrieval should be considered in the evaluation of episodic memory.